Assessment of the effect of eperisone hydrochloride (Myonal®) by electromyography and thermography in patients with temporomandibular joint arthrosis - NAKAJIMA, Hiroshi; OKADA, Toshie (Journal of the Japanese Society for the Temporomandibular Joint, 1994)
This Study was designed to investigate the effect of Eperizone hydrochloride in patients with temporomandibular joint arthrosis by means of electromyography and thermography. The subjects-consisted of 110 patients with temporomandibular joint arthrosis of types I to IV, classified according to the criteria of The Japanese Society for Temporomandibular Joint. Type V cases were excluded. Each of the patients were examined by (1) the protocol for patients with temporomandibular joint arthrosis, (2) thermography, and (3) electromyography by Occiuso Master®. The following results were obtained; (1) Clinical symptoms improved, especially in type I cases. (2) The skin temperature of each insertion of the massete muscle was not always balanced. (3) The silent period frequency increased. The results indicated that Eperisone hydrochloride was effective as an antispasmodic agent in patients with temporomandibular joint arthrosis.